Transitional B Cells in Early Human B Cell Development – Time to Revisit the Paradigm? - Martin, Victoria G.; Wu, Yu-Chang Bryan; Townsend, Catherine L.; Lu, Grace H. C.; O’Hare, Joselli Silva; Mozeika, Alexander; Coolen, Anthonius C. C.; Kipling, David; Fraternali, Franca; Dunn-Walters, Deborah K. (Frontiers in Immunology, 2016)
The B cell repertoire is generated in the adult bone marrow by an ordered series of gene rearrangement processes that result in massive diversity of immunoglobulin (Ig) genes, and consequently an equally large number of potential specificities for antigen. As the process is essentially random, then cells exhibiting excess reactivity with self-antigens are generated and need to be removed from the repertoire before the cells are fully mature. Some of the cells are deleted, and some will undergo receptor editing to see if changing the light chain can rescue an autoreactive antibody. As a consequence, the binding properties of the B cell receptor are changed as development progresses through pre-B>>immature>>transitional>>naïve phenotypes. Using long-read, high-throughput, sequencing we have produced a unique set of sequences from these four cell types in human bone marrow and matched peripheral blood and our results describe the effects of tolerance selection on the B cell repertoire at the Ig gene level. Most strong effects of selection are seen within the heavy chain repertoire, and can be seen both in gene usage and in CDR-H3 characteristics. Age-related changes are small and only the size of the CDR-H3 shows constant and significant change in these data. The paucity of significant changes in either kappa or lambda light chain repertoires implies that either the heavy chain has more influence over autoreactivity than light chain and/or that switching between kappa and lambda light chains, as opposed to switching within the light chain loci, may effect a more successful autoreactive rescue by receptor editing. Our results show that the transitional cell population contains cells other than those that are part of the pre-B>>immature>>transitional>>naïve development pathway, since the population often shows a repertoire that is outside the trajectory of gene loss/gain between pre-B and naïve stages.